Analisis Faktor Penyebab Terjadinya Duplikasi Nomor Rekam Medis Rawat Jalan di Puskesmas Kencong Kabupaten Jember - Esa Amanda Setiawan; Rossalina Adi Wijayanti; Atma Deharja; Selvia Juwita Swari (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2020)
Duplication that occurred in the Kencong Public Health Center was 46 files on February 2019, this could beextremely powerful on legality aspect of medical record file interrupted if it happens the legal case. The aimof this research was to analyze and decide the priority causes of the happening duplication by using USG.The variety of this research is qualitative one by using the collection of interviewing data, observation,documentation and brainstorming. The result of this research stated that the case causing priority is by usingUSG method namely, the education of officer whose education qualification is Diploma D3 degree of MedicalRecord had been appropriated. The trial solving that trouble is recruiting the officers whose educationDiploma D3 degree of Medical Record and they need to have the recommendation about more educationespecially for the officers who still have the minimal education or knowledge about medical record side.